Combined suicide and cytokine gene therapy for peritoneal carcinomatosis. Issue 3 (1st September 2000) - Lechanteur, C; Delvenne, P; Princen, F; Lopez, M; Fillet, G; Gielen, J; Merville, M-P; Bours, V
Abstract : BACKGROUND: Gene therapy is a novel approach for the treatment of cancers, and tumours disseminated in the peritoneal cavity are suitable for in situ delivery of a therapeutic gene. AIMS: The efficacy of a therapy combining a suicide gene (herpes simplex virus type I thymidine kinase (HSV-TK)) and cytokine genes was investigated in a model of peritoneal carcinomatosis induced by colon carcinoma cells in syngeneic rats. MATERIAL AND METHODS: Pre-established macroscopic tumours in BDIX rats were treated by intraperitoneal injections of retrovirus producing cells (FLYA13 TK, FLYA13 granulocyte macrophage-colony stimulating factor (GM-CSF), FLYA13 interleukin 12 (IL-12)) and ganciclovir (GCV). RESULTS: TK/GCV treated animals showed a slight increase in survival time (72 days) compared with the control group (63 days) while the association of cytokine and TK/GCV gene therapy resulted in significantly improved survival, with a large proportion of animals remaining tumour free on day 480 (60% and 40% for TK/GCV/GM-CSF and TK/GCV/IL-12 treated animals, respectively). Histological analysis of treated animals showed that the remaining tumour nodes were infiltrated by mononuclear cells but no major differences were observed between the various treatments. Immunohistochemical analysis revealed that lymphoid CD4 + and CD8 + T cells as well as macrophages accumulated outside untreated tumour nodes while CD8 + and CD25 + activated T cells and macrophages heavily infiltrated the tumours after the different treatments. CONCLUSIONS: Our data indicate that combined suicide and cytokine gene therapy is a powerful approach for the treatment of macroscopic peritoneal carcinomatosis.